Evaluation of Conventional Radiography and an Electronic Apex Locator in Determining the Working Length in C-shaped Canals - Jafarzadeh, Hamid; Beyrami, Masoud; Forghani, Maryam (Iranian Endodontic Journal, 2016)
Introduction: The purpose of this in vitro study was to compare the accuracy of working length determination using the apex locator versus conventional radiography in C-shaped canals. Methods and Materials: After confirming the actual C-shaped anatomy using cone-beam computed tomography (CBCT), 22 extracted C-shaped mandibular second molars were selected and decoronated at the cemento-enamel junction. The actual working length of these canals were determined by inserting a #15 K-file until the tip could be seen through the apical foramen and the working length was established by subtracting 0.5 mm from this length. The working length was also determined using conventional analog radiography and electronic apex locator (EAL) that were both compared with the actual working length. The data was statistically analyzed using paired t-test and marginal homogeneity test. Results: There was no significant differences between the working length obtained with apex locator and that achieved through conventional radiography in terms of measuring the mesiolingual and distal canals (P>0.05); while, significant differences were observed in measurements of the mesiobuccal canals (P=0.036). Within ±0.5 mm of tolerance margin there was no significant difference between EAL and conventional radiography. Conclusion: The apex locator was more accurate in determination of the working length of C-shaped canals compared with the conventional radiography. Keywords: C-shaped Canals; Electronic Apex Locator; Radiography; Working Length